Traffic Assessment and Simulation of Jalan Raja Ashman Shah (In Front of Raja Permaisuri Bainun Hospital), Ipoh - Mazlan, Nursyakirin; Othman, Mohd Hanifi (Recent Trends in Civil Engineering and Built Environment, 2021)
In Malaysia, traffic congestion is a common problem that often occur during rush hours that leading to adverse social, economic, and environmental issues. Ipoh, the fourth largest city in Malaysia is also not spared from experiencing traffic congestion which might happen due to high traffic volume and illegal parking along the road itself especially at the Jalan Raja Ashman Shah (In front of Raja Permaisuri Bainun Hospital).  Therefore, this study was conducted to determine the speed and traffic volume at the Jalan Raja Ashman Shah (In front of Raja Permaisuri Bainun Hospital) at Ipoh town, to develop traffic simulation of the case study location using VISSIM 2020 (SP10) Student Version softwarea nd to propose a mitigation action to reduce or control the congestion issues at the Jalan Raja Ashman Shah (In front of Raja Permaisuri Bainun Hospital), Ipoh. The simulation model has been carried out to analyse the LOS of the study location during the peak hour in the morning, noon and evening. Results showed, LOS at the study location was F that cause delay during peak hour.  Through observation, the congestion occurred due to the irresponsible attitude of road users who parked vehicles illegally on the side of the road and also due to the bottleneck phenomenon. From the result of the LOS of study location, an improvement had been suggested, by implemented of law enforcement to prevent illegal parking alongside of the study location, additional lane along Jalan Raja Ashman Shah (In front of Raja Permaisuri Bainun Hospital) and lastly the combination of law enforcement and lane addition. Combination of law enforcement and lane addition are selected as the suitable improvement method since LOS enhancement is much better than the other two approaches and the increased on the level of service of the study location improved to LOS C.